Gene transfer of neuronal nitric oxide synthase to carotid body reverses enhanced chemoreceptor function in heart failure rabbits. - Li, Y; Li, Y; Liu, D; Cornish, K; Patel, K; Zucker, I; Channon, K; Schultz, H (2005)
Our previous studies showed that decreased nitric oxide (NO) production enhanced carotid body (CB) chemoreceptor activity in chronic heart failure (CHF) rabbits. In the present study, we investigated the effects of neuronal NO synthase (nNOS) gene transfer on CB chemoreceptor activity in CHF rabbits. The nNOS protein expression and NO production were suppressed in CBs (P<0.05) of CHF rabbits, but were increased 3 days after application of an adenovirus expressing nNOS (Ad.nNOS) to the CB. As a control, nNOS and NO levels in CHF CBs were not affected by Ad.EGFP. Baseline single-fiber discharge during normoxia and the response to hypoxia were enhanced (P<0.05) from CB chemoreceptors in CHF versus sham rabbits. Ad.nNOS decreased the baseline discharge (4.5+/-0.3 versus 7.3+/-0.4 imp/s at 105+/-1.9 mm Hg) and the response to hypoxia (18.3+/-1.2 imp/s versus 35.6+/-1.1 at 40+/-2.1 mm Hg) from CB chemoreceptors in CHF rabbits (Ad.nNOS CB versus contralateral noninfected CB respectively, P<0.05). A specific nNOS inhibitor, S-Methyl-L-thiocitrulline (SMTC), fully inhibited the effect of Ad.nNOS on the enhanced CB activity in CHF rabbits. In addition, nNOS gene transfer to the CBs also significantly blunted the baseline renal sympathetic nerve activity (RSNA) and the response of RSNA to hypoxia in CHF rabbits (P<0.05). These results indicate that decreased endogenous nNOS activity in the CB plays an important role in the enhanced activity of the CB chemoreceptors and peripheral chemoreflex function in CHF rabbits.